Hemolysis From Intravenous Immunoglobulin in Obese Patients With Kawasaki Disease - Van Anh, Khanh-Van Y.; Shah, Saloni; Tremoulet, Adriana H. (Frontiers in Pediatrics, 2020)
Objective: We assessed the risk of IVIG-associated hemolytic anemia in patients with acute Kawasaki disease (KD) and evaluated the risk of weight-based dosing in our obese patients. Methods: IVIG-associated hemolytic anemia was assessed in acute KD patients treated with IVIG at Rady Children’s Hospital-San Diego. Patients in whom hemolytic anemia was suspected had a decrease in z-score of their hemoglobin (zHgb) at least two standard deviations below the cohort’s mean change in zHgb from baseline to 2 weeks post-IVIG treatment. These patients were further evaluated for spherocytosis, blood type, need for transfusion, red cell distribution width, reticulocytosis, and direct Coombs test. Body mass index was calculated. Results: Of the 30 IVIG-resistant KD patients who received a second dose of IVIG, 2 (6.7%) developed hemolytic anemia after a total of 4 g/kg of IVIG dosed on actual body weight, or a mean of 4.6 g/kg of IVIG based on lean body mass. Compared to 496 non-obese KD patients who received a single dose of IVIG with no cases of hemolytic anemia, two (5.6%) of 36 obese KD patients developed hemolytic anemia after a single dose of IVIG (2 g/kg) dosed on actual body weight, or a mean of 2.7 g/kg IVIG based on lean body mass. Conclusions: In addition to following patients carefully for hemolytic anemia after a second dose of IVIG, physicians should consider IVIG dosing based on lean body mass for obese patients.